A landscape analysis of HIV cure-related clinical trials and observational studies in 2018 - Liz Barr; Richard Jefferys (Elsevier, 2019)
Objectives: The community-based organisation Treatment Action Group has established an online listing of HIV cure-related trials and observational studies derived from trial registries. Our objective was to use the listing as a basis for a landscape analysis of the current status of HIV cure-related clinical research. Methods: Trials and observational studies listed as of August 2018 formed the sample set. Survey questions were developed on trial development, trial design, recruitment, enrolment, study completion and dissemination plans. A survey was sent to the contact(s) for each study. Supplemental information was collected from clinicaltrials.gov. The full dataset was then analysed. Results: A total of 99 interventional trials and 29 observational studies were included. Diverse interventions are under evaluation, including combinations of experimental candidates. Current studies plan to enrol over 7000 participants. Projected completion dates for ~90% of the sample fell between the fourth quarter of 2018 and the end of 2020. Potential obstacles to enrolment that were reported included concerns over invasive procedures and lack of potential benefit to participants. Data on the sex and ethnicity of enrollees were limited but sufficient to note a significant under-representation of women. Conclusions: A considerable amount of HIV cure-related clinical research is under way. The results from these studies, which should help shape the future of the field, will become available over the next 2-4 years. Diversity both geographically and in terms of enrollees remains limited, particularly in terms of the participation of women, a concern that could significantly affect the generalisability of the findings.